Climate Change Mitigation in the Arfak Mountains through Igya Ser Hanjob: A Legal and Socioecological Review - Pandori, Musa; Roberth KR Hammar; Christina Samangun (Golden Ratio of Law and Social Policy Review, 2025)
Using a juridical and socioecological approach, this study examines the role of the Igya Ser Hanjob customary legal system in mitigating climate change in the Arfak Mountains, West Papua. Igya Ser Hanjob, which literally means "guarding boundaries," is the local wisdom of the Hatam people that regulates land management and environmental conservation in a balanced, sustainable manner, and contains deep spiritual values. This system regulates no-go zones, land rotation management, prohibitions on felling large trees, and an effective community oversight mechanism for maintaining biodiversity and ecosystem stability. The study employed qualitative methods, including in-depth interviews with four Hatam tribal leaders, participant observation, and reviewing relevant national and regional legal documents. Thematic analysis was applied to uncover ecological principles, adaptation practices, and the challenges and external support faced by Igya Ser Hanjob. The results indicate that although this customary legal system has received normative recognition in the constitution and several national regulations, its implementation remains suboptimal due to obstacles to administrative recognition, the lack of specific regional regulations, and the minimal involvement of indigenous communities in the legislative process. This phenomenon has resulted in the potential of local wisdom for climate mitigation not being fully realized. At the same time, pressures of exploitation and development have the potential to threaten the sustainability of the Arfak Mountains ecosystem. Discourse analysis reveals that Igya Ser Hanjob serves as a discourse that integrates the ecological and spiritual values of indigenous communities, while also serving as a platform for negotiation between customary law and formal law, which often marginalizes the role of indigenous communities. This study emphasizes the importance of stronger integration of customary law with national climate change mitigation policies through formal recognition, participatory mapping, and strengthening the legal capacity of indigenous communities. This approach strengthens ecological protection and empowers indigenous communities as primary guardians of a sustainable environment. Thus, this study confirms the relevance of Igya Ser Hanjob as a foundation for ecological ethics and law that can serve as an effective local strategy in addressing climate change and encouraging inclusive and contextual environmental policy reform in West Papua.